Perancangan Sistem Informasi Keuangan Dalam Penyaluran Bantuan Langsung Tunai Dana Desa (BLT-DD) Desa Cikuya Tahun Anggaran 2021 Berbasis Visual Basic - Aulia Widhi Anty (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
The study was carried out in the West Java Province's Cikuya Village, Cicalengka District, Bandung Regency. Qualitative approach is used in this research and data collection used is literature study, interview and observation. The development life cylce system is used for the system depelopment methode with the waterfall modeling. One of the government’s efforts in the village aid distribution program is to provide direct cash assistance through the implementation of a direct cash assistance policy whose funds are sourched from village funds, based on the result of the study, the problem of distributing aid in data management and the distribution process is still done manually so that is slows down the work. The author provides a solution to this problem, namely in the form of a Microsoft access database and a financial information system for direct distribution of Village funds based on VisualBasic 2010. Because only the village goverenment will need this sustem, the author intends to use Microsoft Visual Basic 2010 software and Microsoft Access database. This information system is expected to facilitate the process of distributing direct cash assstance from village funds.